A multi-sensory approach for higher education business students: Using colour in the reading process to analyse academic writing - Susie Marriott (Educational Futures, 2022)
The paper shows a simple approach used to help with reading and analysing academic papers. Initially used with dyslexic students, its use with business students new to researching in higher education proved highly effective and should be applicable to wider subjects. While there is much in the literature about students completing their own academic writing, and good support from books and videos showing them how to do this, there is little published research which outlines or helps students to read, analyse or understand academic resources and then use them effectively. This can be particularly problematic for students new to research as academic journals present a wide range of topics using different styles and methods. This article demonstrates how a multi-sensory approach to reading used with dyslexic students also helps other students to highlight, consolidate, and organise information by the careful use of colour-coding. It has proved particularly useful to students doing their first literature review. The multi-sensory method uses colours to enhance black and white text found in academic journal articles for better organisation of information, to highlight words, sentences, figures, and other information of significance and to navigate longer or more complicated texts to enhance the quality of their own work. The process of using coloured highlighters for coding and organisation is demonstrated here to help incorporate academic information into written assignments.